The Fermi level as an energy reference in liquid jet X-ray photoelectron spectroscopy studies of aqueous solutions. Issue 30 (25th July 2021) - Pérez Ramírez, Lucía; Boucly, Anthony; Saudrais, Florent; Bournel, Fabrice; Gallet, Jean-Jacques; Maisonhaute, Emmanuel; Milosavljević, Aleksandar R.; Nicolas, Christophe; Rochet, François
Abstract : Adding a known redox couple to an aqueous solution gives liquid-jet XPS a natural energy reference, the Fermi level. Abstract : To advance the understanding of key electrochemical and photocatalytic processes that depend on the electronic structure of aqueous solutions, X-ray photoemission spectroscopy has become an invaluable tool, especially when practiced with liquid microjet setups. Determining vertical ionization energies referenced to the vacuum level, and binding energies referenced to the Fermi level, including the much-coveted reorganization energy of the oxidized species of a redox couple, requires that energy levels be properly defined. The present paper addresses specifically how the vacuum level "just outside the surface" can be known through the energy position of the rising edge of the secondary electrons, and how the Fermi level reference is uniquely determined via the introduction of a redox couple. Taking the case of the ferricyanide/ferrocyanide and ferric/ferrous couples, this study also tackles issues related to the electrokinetic effects inherent to the production of a liquid jet in a vacuum, which has become the standard water sample environment for photoemission experiments.